Secondary Hypertension Induced by Vitamin D3: A Case Report and Literature Review - Seyyed Javad Boskabadi; Saeed Kargar-Soleimanabad; Sahar Khosravi; Mohammad Parsa-kondelaji; Farhad Gholami (Mazandaran University of Medical Sciences, 2023)
Background: The effects of vitamin D on the skeletal system, biological metabolism, and immune system function are well shown. Cholecalciferol (vitamin D2) and ergocalciferol (vitamin) are 2 major types of vitamin D. Vitamin D3 deficiency is worldwide and the intoxication induced by it is very rare. Conclusion: Vitamin D3 is involved in calcium hemostasis. The effects of acute hypercalcemia on blood pressure were established. Hypercalcemia can elevate the blood pressure, and renal failure may predispose the individual to a hypertensive response. The clinical symptoms often associated with vitamin D3 intoxication are related to acute renal failure. Hypertension without acute renal failure symptoms can emphasize the relationship between acute hypercalcemia and hypertension.